2020
DOI: 10.1371/journal.pone.0231003
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-infiltrating immune cells in hepatocellular carcinoma: Tregs is correlated with poor overall survival

Abstract: Systematic interrogation of tumor-infiltrating immune cells (TIICs) is key to the prediction of clinical outcome and development of immunotherapies. However, little is known about the TIICs of hepatocellular carcinoma (HCC) and its impact on the prognosis of patients and potential for immunotherapy. We applied CIBERSORT of 1090 tumors to infer the infiltration of 22 subsets of TIICs using gene expression data. Unsupervised clustering analysis by 22 TIICs revealed 4 clusters of tumors, mainly defined by macroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 49 publications
3
43
0
Order By: Relevance
“…This finding is consistent with several studies that also report an association between high levels of Treg infiltration and poor prognosis and response to treatment in a variety of different cancer types, including breast cancer, cervical cancer, and melanomas (133)(134)(135). In 2020, Yu et al also reported a greater-than-3-fold increase in Treg populations in tumor tissues compared to adjacent healthy tissues, further implicating Tregs in HCC development (132). In another study, a higher proportion of Treg tumor infiltration in HCC tumors was also associated with poor tissue differentiation and advanced stages of hepatic fibrosis (136).…”
Section: Targeting Enclysis In Liver Cancersupporting
confidence: 88%
See 1 more Smart Citation
“…This finding is consistent with several studies that also report an association between high levels of Treg infiltration and poor prognosis and response to treatment in a variety of different cancer types, including breast cancer, cervical cancer, and melanomas (133)(134)(135). In 2020, Yu et al also reported a greater-than-3-fold increase in Treg populations in tumor tissues compared to adjacent healthy tissues, further implicating Tregs in HCC development (132). In another study, a higher proportion of Treg tumor infiltration in HCC tumors was also associated with poor tissue differentiation and advanced stages of hepatic fibrosis (136).…”
Section: Targeting Enclysis In Liver Cancersupporting
confidence: 88%
“…Different stages of HCC pathogenesis have been linked to distinct signatures of tumor-infiltrating immune cell populations (131). A large-scale analysis of tumor-infiltrating immune cells in 1090 HCC tumors revealed that greater intratumoural Treg populations were strongly correlated with poorer patient outcomes (132). This finding is consistent with several studies that also report an association between high levels of Treg infiltration and poor prognosis and response to treatment in a variety of different cancer types, including breast cancer, cervical cancer, and melanomas (133)(134)(135).…”
Section: Targeting Enclysis In Liver Cancermentioning
confidence: 99%
“…Furthermore, ICOS + FOXP3 + Tregs contribute to the immunosuppressive HCC microenvironment and lead to an unfavourable prognosis for HCC patients (76). Thus, removal or reduction of the Treg cell population, or inhibition of CD4 + CD25 ++ Treg function in the HCC microenvironment may facilitate the efficacy of tumour immunotherapy (77). In addition, the Th17/Treg ratio is a risk factor for HCC (78).…”
Section: Hepatocellular Carcinoma (Hcc) and Tregsmentioning
confidence: 99%
“…Tregs cells, one of the important constituents of the HCC tumour microenvironment, cognate with a reduction in density and functioning of CD8+ T-cells, hence a therapeutic measure targeting Tregs would not only help in establishing of antitumour immune responses but can also improve survival [56,57]. Studies have outlined a significant decline in levels of intra-tumoural and circulating Tregs cells following radiofrequency ablation or radiofrequency based resection of HCC tumour and an associated improvement in survival [58].…”
Section: Hcc Tumour Microenvironment and Changes In Cytokines Milieumentioning
confidence: 99%